Teaching families to manage intake of candy in the home: Results from a feasibility study using multiphase optimization strategy (MOST) - J. S. Savage; E. L. Adams; B. Y. Rollins; J. A. Bleser; M. E. Marini (Wiley, 2020)
Summary Background Excess intake of desserts/sweets high in added sugars, such as candy, is linked with greater obesity risk. Parents often limit their childrens' intake of these sweet foods using controlling feeding practices, such as restriction; yet, restrictive feeding practices are counterproductive for childrens' self‐regulation of energy intake. Objective This study developed a family‐based behavioural intervention that taught parents alternatives to restrictive feeding practices and encouraged children to consume candy in moderation. Methods Using the multiphase optimization strategy (MOST), parent-child dyads (N = 37) were randomized into one of eight conditions that included a combination of intervention components delivered over 4 weeks: home supply, parent shared decision making, child mindfulness and child attention control strategies. Results Retention rate at follow‐up was high (95%). Among parents who received parent shared decision making, 86.4% reported the structured‐based candy routine they set with their child was easy to follow. Most children reported child mindfulness (95%) and attention control (89.5%) strategies were easy to play. Children recalled 4.1 ± 1.8 of the six mindfulness strategies and 2.7 ± 1.6 of the five attention control strategies at follow‐up. Eating in the absence of hunger tended to be lower for children who received parent shared decision making and child mindfulness components. Conclusion This intervention was feasible and well‐implemented in the home environment. Findings will inform future, larger interventions designed to test similar strategies on childrens; eating behaviours and self‐regulation.